Assessment of gaps in transfer of water management technology in rice grown in the Chambal command of south-eastern Rajasthan - Narolia, R.S.; Singh, Pratap; Mathur, I.N.; Tetarwal, J.P. (Annals of Agricultural Research, 2014)
On-farm experiments were carried out during kharif season of 2006 to 2010 at farmer’s field in Chambal command area under operational research programme of Agricultural Research Station, Kota (Rajasthan). Main aim of the study was to assess the impact of improved water management technology (IWMT) on the productivity and sustainability of rice. Treatments comprised irrigation of 5 Â± 2 cm standing water and refilling at 1-3 days after disappearance of ponding water (Improved technology) which was compared with the farmers’ practice (FP) i.e. continuous submergence (FP). Improved water management technology resulted in 6 % higher mean grain yield (3.74 t/ha) than FP (3.52 t/ha). Pooled data revealed that sustainability yield index (0.853) and sustainability value index (0.544) over five years under IWMT increased to the tune of 5.4 and 6.9 % as compared to FP. Water expanse efficiency (43 kg/ha-cm) and mean incremental cost benefit ratio (4.8) were also better in IWMT than FP.